Optimal Parameters for Preparation of Magnesium Chloride Whisker Composites Using Metal Ion Catalysis Method - Zhu, Pinghua; Zeng, Shuoran; Wang, Lei (Asian Journal of Chemistry, 2014)
Magnesium chloride purified from bittern is selected as the raw material and the influencing factors of basic magnesium chloride whiskers prepared using a metal ion catalysis method at normal pressure are investigated. The effects of the intensity of metal ions, the reaction temperature and the addition of inoculating seeds on the preparation of magnesium chloride whiskers are studied carefully and the morphology of basic magnesium chloride whiskers is analyzed using a scanning electron microscope. It is found that the optimum parameters for the preparation of basic magnesium chloride whiskers using a metal ion catalysis method at normal pressure are as follows: Zn2+ concentration of 30-60 × 10-6 mol/L, reaction temperature of 50 °C and percentage of added inoculating seeds of 0.06 %.